Enhancing ecosystem services in agriculture: the special role of legume intercropping - Metaxia Kokkini; Ioannis Gazoulis; Ioannis Gazoulis; Marios Danaskos; Vasiliki Kontogeorgou; Panagiotis Kanatas; Ilias Travlos (Frontiers in Sustainable Food Systems)
Sustainable agriculture confronts significant challenges such as soil degradation, intensification of agricultural production, and the impact of climate change. Legume intercropping is an “underestimated” cultural practice that harnesses the unique ecosystem services of legumes to enhance resilience and productivity of cropping systems. Legumes contribute to biodiversity by supporting beneficial insects, including pollinators, which can enhance crop productivity. Additionally, through nitrogen fixation, legumes reduce synthetic fertilizer inputs, promote efficient nutrient cycling, and improve soil health. The introduction of legumes in intercropping schemes has beneficial effects on soil texture, microbial diversity, water retention, crop growth, and yield. This cultural practice also contributes to reduced emissions of greenhouse gases, carbon sequestration, and lower pesticide inputs. In addition, legume intercropping promotes biodiversity while facilitating natural pest control and weed suppression. Overall, the inclusion of legumes in intercropping schemes and diversified cropping systems can support food security and mitigate environmental risks related to climate change.